2019
DOI: 10.30721/fsab2019.v2.i1.67
|View full text |Cite
|
Sign up to set email alerts
|

Risk from Staphylococcus aureus in informally marketed raw cow milk

Abstract: This study aimed to investigate the presence of Staphylococcus spp. and Staphylococcus aureus in raw cow milk samples taken from peddlers of five regions in Bulgaria. The results showed that all 44 samples tested were positive for Staphylococcus spp. All isolates were tested for coagulase production and subjected to PCR analysis. PCR amplification of 16S rRNA and nuc genes found the presence of Staphylococcus aureus in 23 (52.3%) of a total of 44 raw milk samples. The number of Staphylococcus spp. ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In Southern Bulgaria 44 raw milk samples were studied and were found that 52.3% to be contaminated with S. aureus. The authors did not analyse the presence methicillin resistance, but concluded that poor hygiene practices throughout the food chain and large number of Staphylococcus aureus (3.4 × 10 4 cfu/g) could be a risk to human health (Bangieva and Rusev 2019). The artisanal cheese sold in informal markets in Kosovo also showed a high prevalence of coagulase positive Staphylococcus aureus (Studenica et al 2022).…”
Section: Prevalence Of Mrsa In Foodmentioning
confidence: 99%
“…In Southern Bulgaria 44 raw milk samples were studied and were found that 52.3% to be contaminated with S. aureus. The authors did not analyse the presence methicillin resistance, but concluded that poor hygiene practices throughout the food chain and large number of Staphylococcus aureus (3.4 × 10 4 cfu/g) could be a risk to human health (Bangieva and Rusev 2019). The artisanal cheese sold in informal markets in Kosovo also showed a high prevalence of coagulase positive Staphylococcus aureus (Studenica et al 2022).…”
Section: Prevalence Of Mrsa In Foodmentioning
confidence: 99%